Helical reconstruction in a post human bite defect - Soni, A; Sheoran, S; Rajput, A (Indian Journal of Plastic Surgery, 2006)
A case of a post traumatic partial defect of the helix of ear and its reconstruction by using a post auricular bipedicled tube flap, in stages is reported.
Keywords: Partial traumatic defect; helix; staged correction; tube flap; post auricular